Antimetastatic and Anti-Inflammatory Potentials of Essential Oil from Edible Ocimum sanctum Leaves - Thamilvaani Manaharan; Ramaraj Thirugnanasampandan; Rajarajeswaran Jayakumar; Gunasekar Ramya; Gogul Ramnath; M. S. Kanthimathi (The Scientific World Journal)
Antimetastatic and anti-inflammatory activities of Ocimum sanctum essential oil (OSEO) have been assessed in this study. OSEO at the concentration of 250 μg/mL and above showed a significant (P*<0.05) decrease in the number of migrated cancer cells. In addition, OSEO at concentration of 250 μg/mL and above suppressed MMP-9 activity in lipopolysaccharide (LPS) induced inflammatory cells. A dose-dependent downregulation of MMP-9 expression was observed with the treatment of OSEO compared to the control. Our findings indicate that OSEO has both antimetastatic and anti-inflammatory potentials, advocating further investigation for clinical applications in the treatment of inflammation associated cancer.